GROWTH ANALYSIS OF WRONSKIANS BASED ON RELATIVE \(L^*\)-ORDER AND RELATIVE \(L^*\)-TYPE - Datta, Sanjib Kumar; Biswas, Tanmay; Biswas, Chinmay (Italian Journal of Pure and Applied Mathematics, 2015)
In this paper, we establish the relationship between the relative L-order (relative L∗-order), relative L-type (relative L∗-type) and relative L-weak type (relative L∗-weak type) of a transcendental meromorphic function f with respect to an entire function g and that of Wronskian generated by the meromorphic f and entire g.